2015
DOI: 10.1038/mp.2014.184
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin, neuronal vulnerability and behavioral emotionality

Abstract: Somatostatin (SST) deficits are common pathological features in depression and other neurological disorders with mood disturbances, but little is known about the contribution of SST deficits to mood symptoms or causes of these deficits. Here we show that mice lacking Sst (SstKO) exhibit elevated behavioral emotionality, high basal plasma corticosterone and reduced gene expression of Bdnf, Cortistatin, and Gad67, together recapitulating behavioral, neuroendocrine and molecular features of human depression. Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
166
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(184 citation statements)
references
References 88 publications
17
166
1
Order By: Relevance
“…Follow-up investigation in the ACC demonstrated reduced SST expression per cell across all cortical layers (83), suggesting a common origin despite SST cell heterogeneity. A putative causal role for reduced SST cell function is supported by work showing that Sst knockout mice recapitulated several MDD hallmarks, including elevated depressive-/anxiety-like behaviors, increased corticosterone, and reduced expression of brain-derived neurotrophic factor ( Bdnf ) and Gad67 genes, although, these changes were not seen in Sst Hz mice, possibly due to compensatory cellular adaptations (85). Note that SST is co-released with GABA, has pre- and post-synaptic physiological and neuronal roles (See review (86)), and when infused into rodent corticolimbic brain regions, has anxiolytic- and antidepressant-like effects (8790).…”
Section: Gaba and Sst Interneuron-related Microcircuit Deficits In Dementioning
confidence: 99%
See 2 more Smart Citations
“…Follow-up investigation in the ACC demonstrated reduced SST expression per cell across all cortical layers (83), suggesting a common origin despite SST cell heterogeneity. A putative causal role for reduced SST cell function is supported by work showing that Sst knockout mice recapitulated several MDD hallmarks, including elevated depressive-/anxiety-like behaviors, increased corticosterone, and reduced expression of brain-derived neurotrophic factor ( Bdnf ) and Gad67 genes, although, these changes were not seen in Sst Hz mice, possibly due to compensatory cellular adaptations (85). Note that SST is co-released with GABA, has pre- and post-synaptic physiological and neuronal roles (See review (86)), and when infused into rodent corticolimbic brain regions, has anxiolytic- and antidepressant-like effects (8790).…”
Section: Gaba and Sst Interneuron-related Microcircuit Deficits In Dementioning
confidence: 99%
“…Mouse models of depression using unpredictable chronic mild stress ( UCMS ) or elevated glucocorticoid exposure recapitulated SST and GABA-related deficits (85). Sex differences have also been implicated, as MDD-related SST reductions are more severe in females (82, 83), who are twice as likely to develop mood disorders (119).…”
Section: Origins Of Sst Deficitsmentioning
confidence: 99%
See 1 more Smart Citation
“…SST interneurons are altered following chronic stress exposure, and dysfunction of these neurons is thought to contribute to depressive symptoms (39,40). Postmortem studies have reported a reduced number of calbindin + (putative SST) interneurons and decreased expression of SST interneuron markers in the PFC (41,42), demonstrating that altered SST/GABA function is associated with depressive symptoms (43).…”
Section: Figure 6 M1-achr Mediates Cholinergic Stimulation Of Sst Inmentioning
confidence: 99%
“…Altered levels and signaling of gamma-aminobutyric acid (GABA), the major inhibitory neurotransmitter, is frequently reported in depression [1, 2], anxiety disorder [3], normal ageing [4], and neurodegenerative disorders, including Alzheimer’s disease [5], and in multiple brain regions including the prefrontal cortex [6] and anterior cingulate cortex [7]. Recent studies showed that such reductions of GABA levels in the human brain are associated with cognitive impairments in an age-dependent manner [8] and are further worsened during older age [9].…”
Section: Introductionmentioning
confidence: 99%